Descriptive Study of Sleep Disorders in Psychiatric Female Patients: A Cross-Sectional Study - Singh, Lakshman (Journal of Biomedical and Pharmaceutical Research, 2019)
Sleep disorders are prevalent among individuals with psychiatric conditions and can significantly impact their mental and physical health. This study aimed to describe the prevalence and types of sleep disorders in female psychiatric patients, assessing the relationship between different psychiatric conditions and sleep disturbances. A total of 120 female patients, aged 18-55 years, diagnosed with various psychiatric conditions such as depression, anxiety, schizophrenia, and bipolar disorder were included. Data was collected using the Pittsburgh Sleep Quality Index (PSQI) and the Insomnia Severity Index (ISI). The study revealed that 75% of the participants experienced some form of sleep disturbance, with insomnia being the most common (45%). Anxiety and depression were significantly correlated with poor sleep quality, while schizophrenia and bipolar disorder also showed notable disruptions in sleep patterns. The results suggest that sleep disorders are common among female psychiatric patients, and improving sleep quality should be an integral part of psychiatric treatment.Keywords: Sleep disorders, psychiatric patients, insomnia, anxiety, depression, female patients, cross-sectional study.